Numerical simulation on nitrogen condensation in high aspect ratio mini-channels. (September 2020) - Sun, Daming; Qin, Shaocong; Shen, Qie; Su, Shiyue; Lei, Shenghui
Highlights: A numerical model of the nitrogen condensation is developed to predict the performance at different practical operations. The fin efficiency η of the tall fins at low temperature (<120 K) can be as high as 0.7. An improved correlation of condensation heat transfer is proposed. The 1 kW cooling power require only 1.5 K temperature difference at 77 K. Abstract: Of importance is the study of the cryogenic condensation as it physically behaves differently owing to the interesting fluid properties of cryogens appearing at extremely low temperature. In the paper, we focus on numerically exploring the nitrogen condensation in mini channels having the high aspect ratio of 12.5 towards the application of the kW-scale cooling power. It is found that the heat transfer rate and coefficient lie in between the Nusselt condensation (NC) and extended surface condensation (ESC) solutions among the selected operational conditions. The numerical results reveal that the longitudinal conduction plays a role. Interestingly, the reversing flow happens as the inlet flow rate is insufficient to satisfy the nitrogen condensation and particularly it becomes dominant at the larger temperature difference. Most importantly, an improved correlation of the cryogenic condensation heat transfer is proposed and strongly suggests that the fin efficiency η can be as high as 0.7, which is different from the expectation that tall fins are ineffective in condensation. In terms of the 1 kW cooling power, the high-aspect-ratio fin exchanger studied just needs the temperature difference of 1.5 K and it can improve 10 times the efficiency of condensation. It is important that the studies can inform the optimization of the cryocoolers.